The Effect Of Employee Engagement and Corporate Culture on Job Satisfaction at PT. Oemah Insan Mandiri - Pramana Agus Sumardianto; Ahmad Mardalis (IAIN Palopo, 2023)
The purpose of this study is to analyze the effect of employee engagement and corporate culture on job satisfaction, so the researcher will take the title